2021
DOI: 10.3892/mmr.2021.12310
|View full text |Cite
|
Sign up to set email alerts
|

SOD2 overexpression in bone marrow‑derived mesenchymal stem cells ameliorates hepatic ischemia/reperfusion injury

Abstract: Hepatic ischemia/reperfusion injury (HIRI) is a complex pathophysiological process that may develop after liver transplantation and resection surgery, as well as in uncontrolled clinical conditions. Bone marrow-derived mesenchymal stem cells (BM-MSCs) are potential targets for liver diseases. Thus, the present study aimed to investigate the effects of superoxide dismutase 2 (SOD2) overexpression in BM-MSCs on HIRI by constructing a HIRI rat model. The adenoviral vector containing SOD2 and the corresponding con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Many studies have reported on developing MSCs expressing antiapoptotic genes to promote cell survival and inhibit apoptosis induced by hypoxia or ROS, including superoxide dismutase 2 (SOD2) [ 238 ], Bcl-2 [ 239 ], and adrenomedullin (ADM) [ 240 ]. In addition, the co-overexpression of VEGF and Bcl-2 genes not only reduced apoptosis and decreased autophagy but also promoted more rapid proliferation in vitro under OGD [ 241 ].…”
Section: Selecting Appropriate Genes For Transductionmentioning
confidence: 99%
“…Many studies have reported on developing MSCs expressing antiapoptotic genes to promote cell survival and inhibit apoptosis induced by hypoxia or ROS, including superoxide dismutase 2 (SOD2) [ 238 ], Bcl-2 [ 239 ], and adrenomedullin (ADM) [ 240 ]. In addition, the co-overexpression of VEGF and Bcl-2 genes not only reduced apoptosis and decreased autophagy but also promoted more rapid proliferation in vitro under OGD [ 241 ].…”
Section: Selecting Appropriate Genes For Transductionmentioning
confidence: 99%
“…For instance, Wang et al [42] indicated that BM-MSCs could protect the rats against IRI by enhancing the autophagy mediated by HO-1 (heme oxygenase-1). In addition, Li et al [43] reported that BM-MSCs with overexpression of superoxide dismutase 2 could attenuate hepatic IRI through inhibiting oxidative stress and apoptosis of hepatocytes. Nowadays, there are two types of immune rejection, including host-versus-graft reaction and graft-versus-host reaction.…”
Section: Immunomodulatory Role Of Mscs In Ltmentioning
confidence: 99%
“…This has been supported by the following observations. First, overexpression of antioxidants such as glutathione peroxidase 1 (GPX1) in ECs [ 142 ], HO-1 [ 143 ] and SOD [ 144 ] reduced the Bax/Bcl-2 ratio in I/R injury of other types of cells. In addition, meldonium, which functions as an antioxidant, decreased the ratio of Bax/Bcl-2, ameliorating I/R-induced kidney injury [ 121 ].…”
Section: Role Of Mitochondrial Function In the Regulation Of Ceramide...mentioning
confidence: 99%
“…As discussed earlier, antioxidants inhibit ceramide-producing enzymes, and conversely the inhibition of antioxidants by ROS activates these enzymes ( Section 4.3 and Section 4.4 ). In addition, overexpression of antioxidants [ 142 , 143 , 144 ] reduced apoptotic-Bcl-2 family proteins that activate ceramide-producing enzymes and increased anti-apoptotic Bcl-2 family proteins that inhibit ceramide-producing enzymes ( Section 5.2 ). Furthermore, a rheostat of ROS-antioxidants can regulate the activity of SphKs ( Section 7.2 ).…”
Section: A Rheostat Of Ceramide-s1p In the Regulation Of Oxidative St...mentioning
confidence: 99%